Representational Difference Analysis to Identify Genomic Differences between Musa Acuminata X Balbisiana Cv Mutiara and Musa Acuminata X Balbisiana Cv Rastali in Relation to Fusarium Tolerance - Yong, Sock Hwa (2009)
Inherited characteristics of an organism are the reflections of gene structure and organization, including interactions among different genes and their products, as well as environmental factors. Thus, variations in other genes may affect the expression or activity of proteins encoded by specific genes. The study of genetic variation is essential in order to examine differences among members of the same species, such as to differentiate between individuals. Musa acuminata x balbisiana cv Rastali is very susceptible to Fusarium Wilt Race 1 and Race 4, which is caused by the soil inhibiting fungus known as Fusarium oxyporum f. sp. Cubense. Micropropagation of Fusarium wilt tolerant M. acuminata x balbisiana cv Rastali selection has been successfully developed by United Plantations Bhd. These bananas have shown a high tolerance to Fusarium wilt race 4 and it is known as M. acuminata x balbisiana cv Mutiara. Fusarium wilt tolerant M. acuminata x balbisiana cv Rastali selection is based on the screening of banana clones by field testing in the “Fusarium Hot-Spot”. The process is time consuming and the process may result in a disease outbreak. Thus, polymorphic markers to differentiate M. acuminata x balbisiana cv Rastali from M. acuminata x balbisiana cv Mutiara will facilitate the early identification and screening process. In this study, representational difference analysis (RDA) approach has been used to identify genomic differences between M. acuminata x balbisiana cv Mutiara and M. acuminata x balbisiana cv Rastali. A total of 56 difference products were isolated from the variable sequences present in the genomes of both cultivars with two enzymes and four subtractions. These clones were selected for sequencing and homology search against the available databases. Generally, the two cultivars showed a high degree of genomic similarity (identities > 98 %). Base changes and short deletions of DNA sequences of both cultivars were detected by the sequence analysis of 8 interesting clones that were expressed during the infection of M. acuminata x balbisiana cv Mutiara. One of the prospective clone, 1.2-5b is homologous to chitinase class III which is a plant defence related gene. It was found to only express in the root of infected M. acuminata x balbisiana cv Mutiara although it was present in both M. acuminata x balbisiana cv Mutiara and M. acuminata x balbisiana cv Rastali genomic DNA. The amplified DNA fragment using primer 1.2-5b for both cultivars is different in length. The most variable region was found at the sequence after the specific forward primer site and the identity of sequence was found at the second half of the sequence. Besides, primer 2.2-9 also gave a different amplified product size, whereby the amplified fragment of M. acuminata x balbisiana cv Mutiara is 25 bp longer than the M. acuminata x balbisiana cv Rastali. Homology search of the sequence from M. acuminata x balbisiana cv Mutiara was unknown. Both cultivars can be easily distinguished from each other by using primers 1.2-5b and 2.2-9. The highly variable region in the sequence of 1.2-5b and 2.2-9 for both cultivar might be due to the natural mutation and environment stresses for the M. acuminata x balbisiana cv Mutiara which derived from M. acuminata x balbisiana cv Rastali to be Fusarium tolerance and survived. The RDA approach has successfully isolated and identified potential variable regions of DNA fragments that might be related to their genotype as Fusarium wilt tolerant and Fusarium wilt susceptible cultivars.